Factors associated with parental intention to vaccinate their primary school-aged children in Indonesia - Emma Mohamad,; Arina Anis Azlan,; Elly Yuliawati,; Andi Muhammad Tri Sakti, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Along with the consistent increase in the COVID-19 vaccination rate, the Indonesian government continues to strive to control the pandemic with various policy programmes. On the other hand, the vaccination programme has also been expanded to 6-11 years school children to foster the implementation of school reopening despite many debates and controversies circulated in the country. Identifying parental health beliefs toward vaccination, this study aims to examine factors influencing parental intention to vaccinate their children. An online survey was conducted to attain responses from 400 study participants from 9 selected provinces. The data were analysed using descriptive and inferential statistical techniques on the SPSS version 26. This study revealed that vaccination acceptance is high among parents in Indonesia. Parents’ intention to vaccinate their children was significantly influenced by health beliefs. The multiple regression analysis suggested perceived susceptibility (β = .146, p = .012), perceived benefits (β = .249, p = .000) and cues to action (β = .220, p = .000) as significant predictors which positively influenced the vaccination intention, while the perceived barrier (β = -.316, p = .000) was identified as a negative predictor of the dependent variable in the model. There was a significant mean difference in parental intention within gender, age group, and household income. The findings of this study emphasised the need to provide a more strategic health messaging and health education programme to address the issues surrounding the barriers to implementing vaccination for children in Indonesia.